Konferencijos „Lietuvos magistrantų informatikos ir IT tyrimai“ darbai - Bernatavičienė , Jolita; Dzemyda, Gintautas; Kurasova, Olga; Žilinskas, Julius (Vilnius University Open Series, 2023)
The conference "Lithuanian MSc Research in Informatics and ICT" is a venue to present research of Lithuanian MSc theses in informatics and ICT. The aim of the event is to raise skills of MSc and other students, familiarize themselves with the research of other students, encourage their interest in scientific activities. Students from Vytautas Magnus University and Vilnius University gave their presentations at the conference.